2017
DOI: 10.1080/01658107.2017.1307995
|View full text |Cite
|
Sign up to set email alerts
|

Three New PAX2 Gene Mutations in Patients with Papillorenal Syndrome

Abstract: Papillorenal syndrome (PAPRS; Mendelian Inheritance in Man [MIM] 120330) is an autosomal dominant disease characterised by the presence of congenital renal and optic nerve abnormalities associated with mutations of the gene. In this article, the authors present four patients with PAPRS who are carriers of three new mutations, as well as another patient with a possible non-pathogenic variant of the gene. All patients were given a full neurophthalmological examination, and all patients underwent a genetic test f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A growing number of studies suggested that transcription factors play an important role in the process of neural development, and multiple genes encoding transcription factors had been identified as risk genes for neurodevelopmental disorders. , The transcription factor encoded by the Pax2 gene is expressed in the kidneys, eyes, ears, and CNS and participates in the differentiation of early neural precursor cells. Mutations in Pax2 result in various diseases, such as renal dysplasia, abnormalities of the optic nerve, , and neurodevelopment disorders, including developmental delays, , epilepsy, , ID, , and ASD . In previous studies, we found that Pax2 +/– mice showed a high level of self-grooming behavior compared with wild-type mice .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A growing number of studies suggested that transcription factors play an important role in the process of neural development, and multiple genes encoding transcription factors had been identified as risk genes for neurodevelopmental disorders. , The transcription factor encoded by the Pax2 gene is expressed in the kidneys, eyes, ears, and CNS and participates in the differentiation of early neural precursor cells. Mutations in Pax2 result in various diseases, such as renal dysplasia, abnormalities of the optic nerve, , and neurodevelopment disorders, including developmental delays, , epilepsy, , ID, , and ASD . In previous studies, we found that Pax2 +/– mice showed a high level of self-grooming behavior compared with wild-type mice .…”
Section: Discussionmentioning
confidence: 85%
“…24,25 The transcription factor encoded by the Pax2 gene is expressed in the kidneys, eyes, ears, and CNS 26−28 and participates in the differentiation of early neural precursor cells. Mutations in Pax2 result in various diseases, such as renal dysplasia, abnormalities of the optic nerve, 29,30 and neurodevelopment disorders, including developmental delays, 31,32 epilepsy, 33,34 ID, 35,36 and ASD. 36 In previous studies, we found that Pax2 +/− mice showed a high level of self-grooming behavior compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not observe retinal haemorrhage or aneurysm formation, the oxygen saturation in larger retinal vessels was a marker of both retinal metabolism and vascular function, and this parameter could contribute to early detection and prevention of the development of microcirculatory dysfunction in CKD. The constellation of optic nerve abnormalities and renal disease has been described in recent years as papillorenal syndrome (PAPRS), an autosomal dominant genetic disorder associated with PAX2 mutations (Parsa et al 2001;Galvez-Ruiz et al 2017). Papillorenal syndrome (PAPRS) was first described in 1977 by Rieger, when it was termed renal coloboma syndrome (Rieger 1977), having later been redefined as PAPRS (Parsa et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The constellation of optic nerve abnormalities and renal disease has been described in recent years as papillorenal syndrome (PAPRS), an autosomal dominant genetic disorder associated with PAX2 mutations (Parsa et al 2001; Galvez‐Ruiz et al 2017). Papillorenal syndrome (PAPRS) was first described in 1977 by Rieger, when it was termed renal coloboma syndrome (Rieger 1977), having later been redefined as PAPRS (Parsa et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“… 37 For example, the deletion of cytosine in exon 5 of patient 13 causes increased gene expression and exhibits seizures ( Table 1 ). The insertion of guanine in exon 2 of patients 3–6, which may cause premature termination of transcription and change the DNA binding function of PD, 21 resulting in insufficient PAX2 haplotypes, affecting protein function, and may cause patients to exhibit developmental delays and intellectual disability. While Pax2 consists of 10 exons spanning approximately 91.7 kb in mice, the corresponding translated peptide sequences of human and mouse exon 6 are identical.…”
Section: Nuclear Transcription Factor Pax2mentioning
confidence: 99%